Third Five Year Plan (1961-66) (Abridged Edition), Himachal Pradesh Administration - Planning Commission (Planning Commission, 1961)
Long before Independence the national leaders foresaw the indispensability of planned development for the full realisation of the fruits of freedom by all classes of the people and, as long ago as 1937, they found time in the midst of the fight for freedom to appoint the “National Planning Committee”, and to fulfill this step by the preparation of a draft outline of a Plan. After Independence, the Government set up, by a resolution, in March, 1950, a permanent Planning Commission for the country. Thus the final seal of approval was put upon the Stale policy of a planned economy as a feature of the nation’s future development.
Himachal Pradesh Administration Planning and Development Department